The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/ppul.22969
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transitions in bronchopulmonary dysplasia of newborn rats

Abstract: EMT of AT2 cells occurred in the hyperoxia-induced newborn rat BPD model and resulted in attenuated alveolar development as a portion of the myofibroblasts accumulated in the lung originated from AT2 cells via EMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 40 publications
(55 reference statements)
8
32
0
Order By: Relevance
“…Moreover, hyperoxia may destruct both the endothelial and the epithelial barriers by downregulating tight junction proteins (20,21). We also observed deposition of extracellular matrix and retarded lung development, as reported in our preview study (22). …”
Section: Discussionsupporting
confidence: 89%
“…Moreover, hyperoxia may destruct both the endothelial and the epithelial barriers by downregulating tight junction proteins (20,21). We also observed deposition of extracellular matrix and retarded lung development, as reported in our preview study (22). …”
Section: Discussionsupporting
confidence: 89%
“…in expression of both protein (P Ͻ 0.01) indicated that hyperoxia also stimulated EMT in cultured AEC II, in accordance with our previous in vivo study concerning EMT in the BPD model (59).…”
Section: Transdifferentiation Of Aec II Isolated From Newborn Rats Wasupporting
confidence: 76%
“…Alveolar epithelial EMT was observed after TGF-␤1 stimulation (35) and in adult idiopathic pulmonary fibrosis (56). Our preliminary study found EMT in lung tissue in a hyperoxiainduced BPD-like animal model (59). The present study has revealed that cultured AEC II also underwent EMT, in addition to transdifferentiation in response to hyperoxia stimulation, which means that AECs travel along several pathways in an hyperoxic environment.…”
Section: Discussionmentioning
confidence: 74%
“…Collectively, the changes in these biomarkers, accompanied by pulmonary morphological changes, are similar to the development of human BPD. The establishment and validation of the hyperoxia‐induced BPD rat model is consistent with previous studies …”
Section: Discussionsupporting
confidence: 88%
“…(7) Up‐down‐regulation (hyperoxia/normoxia): judges whether expression is unchanged, up or down according to the normalized expression. (8) p value: see our difference analysis method used in another study . FDR: corrected p ‐value…”
Section: Resultsmentioning
confidence: 99%